2011
DOI: 10.1128/iai.01203-10
|View full text |Cite|
|
Sign up to set email alerts
|

Nasal Immunization with a Fusion Protein Consisting of the Hemagglutinin A Antigenic Region and the Maltose-Binding Protein Elicits CD11c+CD8+Dendritic Cells for Induced Long-Term Protective Immunity

Abstract: We assessed the efficacy of a fusion protein consisting of the 25-kDa antigenic region of Porphyromonas gingivalis hemagglutinin A and the Escherichia coli maltose-binding protein (25k-hagA-MBP) as a nasal vaccine for the prevention of oral infection with P. gingivalis. Nasal immunization with 25k-hagA-MBP induced high levels of 25k-hagA-specific serum IgG, serum IgA, and salivary IgA antibodies in a Toll-like receptor 4 (TLR4)-dependent manner. These antibody responses were maintained for at least 1 year afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…These results are also in accordance with previous observations that sublingual immunization might favor the induction of both Th1‐type and Th2‐type responses (Cuburu et al ., ; Zhang et al ., ). In contrast, nasal vaccination with 25k‐hagA‐MBP exhibited Th2‐type responses owing to the predominant production of IL‐4 with no IFN‐γ (Du et al ., ). This discrepancy may indicate that the induction of Th1‐type and Th2‐type responses is determined by the route of the vaccine rather than the properties of the vaccine antigens.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These results are also in accordance with previous observations that sublingual immunization might favor the induction of both Th1‐type and Th2‐type responses (Cuburu et al ., ; Zhang et al ., ). In contrast, nasal vaccination with 25k‐hagA‐MBP exhibited Th2‐type responses owing to the predominant production of IL‐4 with no IFN‐γ (Du et al ., ). This discrepancy may indicate that the induction of Th1‐type and Th2‐type responses is determined by the route of the vaccine rather than the properties of the vaccine antigens.…”
Section: Discussionmentioning
confidence: 97%
“…Mice were orally infected with P. gingivalis as described previously (Du et al ., ), with minor modifications. Briefly, mice were given ad libitum access to ionized water containing sulfamethoxazole/trimethoprim (Sulfatrim; Goldline Laboratories, Fort Lauderdale, FL) at 10 mL per pint for 10 days.…”
Section: Methodsmentioning
confidence: 99%
“…MBP has been used as a chaperone component in vaccines to enhance antigen-specific humoral and cellular immune responses in immunized animals [ 2 , 3 , 4 , 5 , 6 , 7 ]. In addition to the immunostimulatory role, previous studies have also shown that MBP provides intrinsic maturation stimulus to DCs [ 7 ], induces Th1 cell activation, and increases the production of NO in mouse peritoneal macrophages [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…When fused with a recombinant protein, MBP can increase the solubility of the fusion protein by a poorly understood mechanism, and thus is commonly used to improve the yield, facilitate the purification and enhance the stability of fusion proteins [ 2 , 3 ]. Recently, MBP has been used as a chaperone component in various vaccines against pathogenic bacteria and viruses to enhance the immunogenicity of recombinant protein-MBP fusion protein vaccines [ 4 , 5 , 6 ]. MBP has been shown to induce dendritic cell (DC) activation and production of proinflammatory cytokines [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…High salivary IgA antibodies to A. naeslundii, reduction in bone loss Crawford et al (1978) Purified fimbriae and fimbrial subunit from Porphyromonas gingivalis Parenteral immunization of rats Decreased bone loss; serum IgG, salivary IgA antibody Evans et al (1992b) Th2-type-specific T cell clone anti-Aggregatibacter actinomycetemcomitans Nasal immunization of mice Significant serum IgG, IgA, and salivary IgA anti-HagA antibody for at least 1 year; also significant reduction in alveolar bone loss for 1 year after immunization Du et al (2011) the design of vaccines for dental caries has been to select antigens that are of the most significance in the molecular pathogenesis of the disease. In the case of PD, antigen selection is more complex.…”
Section: Whole Cells Of Actinomyces Naeslundiimentioning
confidence: 97%